PENDAMPINGAN PEMBUKUAN SEDERHANA UNTUK MENINGKATKAN PEMAHAMAN PENYUSUNAN LAPORAN KEUANGAN - Ade Sagita Damayanti; Ratna Purnama Sari; Rahandhika Ivan Adyaksana; Yennisa (Jurnal Berdaya Mandiri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) often face challenges in preparing financial reports because these processes are still manual and unstructured. This study aims to improve MSMEs' understanding of financial reporting and to analyze the effectiveness of Microsoft Excel. The method used was a descriptive quantitative approach using observation, interviews, documentation, and questionnaires. The activities were carried out through the stages of initial observation, needs identification, training and mentoring, and implementation. The results showed that, before the mentoring, financial records were disorganized and not integrated with the owner's finances. After the mentoring, business owners were able to systematically record transactions and prepare simple financial reports, including profit and loss statements, changes in equity, and the financial position. The use of Microsoft Excel has been shown to improve the accuracy and neatness of recording and to foster awareness of separating business and personal finances. Therefore, Microsoft Excel-based mentoring is effective in improving the quality of MSME financial management. Keyword: MSMEs, financial reports, Microsoft Excel, bookkeeping